Pengaruh Permainan Outbound Terhadap Perkembangan Sosial Anak di Taman Kanak-Kanak Kemala Bhayangkari 03 Alai Padang - Aisyah Rahmadani; Yaswinda Yaswinda (Program Studi PGRA, 2019)
The purpose of this study was to determine the effect of outbound games on the social development of children in kindergarten Kemala Bhayangkari 03 Alai Padang. This research is a quantitative study with a Quasi Experiment approach. The population of this research was all children in Kemala Bhayangkari 03 Alai Padang Kindergarten, Purposive sampling technique, namely class B5 and B6, each of which amounted to 12 children. Data collection techniques using observation. Then the data is processed with a difference test (t-test). Based on data analysis, the experimental class test average was 82.81 and SD was 6.81 while the control class was 69.27 and SD was 5.96 on the hypothesis testing obtained t count (4.97794 and t table 2) , 07387) at the real level α = 0.05 and dk = 22. It can be concluded that outbound games affect the social development of children in kindergarten Kemala Bhayangkari 03 Alai Padang in the 2018/2019 school year.